Attitudes Toward Financial Control Systems in the United States and Japan - Daley, Lane; Jiambalvo, James; Sundem, Gary L.; Kondo, Yasumasa (Journal of International Business Studies, 1985)
Recently researchers have begun to investigate issues of differences in the use of managerial accounting tools across differing national environments. Much of this research is of the case study approach documenting actual practices for a small group of firms, or a distillation from numerous observations but using anecdotal evidence to support various conjectures.